Streptococcus pneumoniae Affects Endothelial Cell Migration in Microfluidic Circulation - Kopenhagen, Anna; Ramming, Isabell; Camp, Belinda; Hammerschmidt, Sven; Fulde, Marcus; Müsken, Mathias; Steinert, Michael; Bergmann, Simone (Frontiers in Microbiology, 2022)
Bloodstream infections caused by Streptococcus pneumoniae induce strong inflammatory and procoagulant cellular responses and affect the endothelial barrier of the vascular system. Bacterial virulence determinants, such as the cytotoxic pore-forming pneumolysin, increase the endothelial barrier permeability by inducing cell apoptosis and cell damage. As life-threatening consequences, disseminated intravascular coagulation followed by consumption coagulopathy and low blood pressure is described. With the aim to decipher the role of pneumolysin in endothelial damage and leakage of the vascular barrier in more detail, we established a chamber-separation cell migration assay (CSMA) used to illustrate endothelial wound healing upon bacterial infections. We used chambered inlets for cell cultivation, which, after removal, provide a cell-free area of 500 μm in diameter as a defined gap in primary endothelial cell layers. During the process of wound healing, the size of the cell-free area is decreasing due to cell migration and proliferation, which we quantitatively determined by microscopic live cell monitoring. In addition, differential immunofluorescence staining combined with confocal microscopy was used to morphologically characterize the effect of bacterial attachment on cell migration and the velocity of gap closure. In all assays, the presence of wild-type pneumococci significantly inhibited endothelial gap closure. Remarkably, even in the presence of pneumolysin-deficient pneumococci, cell migration was significantly retarded. Moreover, the inhibitory effect of pneumococci on the proportion of cell proliferation versus cell migration within the process of endothelial gap closure was assessed by implementation of a fluorescence-conjugated nucleoside analogon. We further combined the endothelial CSMA with a microfluidic pump system, which for the first time enabled the microscopic visualization and monitoring of endothelial gap closure in the presence of circulating bacteria at defined vascular shear stress values for up to 48 h. In accordance with our CSMA results under static conditions, the gap remained cell free in the presence of circulating pneumococci in flow. Hence, our combined endothelial cultivation technique represents a complex in vitro system, which mimics the vascular physiology as close as possible by providing essential parameters of the blood flow to gain new insights into the effect of pneumococcal infection on endothelial barrier integrity in flow.